2005
DOI: 10.1093/jn/135.6.1486
|View full text |Cite
|
Sign up to set email alerts
|

Fos-Positive Neurons Are Increased in the Nucleus of the Solitary Tract and Decreased in the Ventromedial Hypothalamus and Amygdala by a High-Protein Diet in Rats

Abstract: Transition from a normal- (NP) to a high-protein (HP) diet induces a rapid depression in food intake and a progressive but incomplete return to the initial intake during the succeeding days. The aim of this study was to determine which CNS regions are involved in the HP diet-induced satiety in rats. Brains were collected from 3 groups of adult rats after habituation to an NP diet (21 d), during the transition phase to a HP diet (2 d), or after habituation to the HP diet (21 d). Fos expression was measured in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…enough to overcome changes in food intake related to novelty and differences in palatability (Jean et al ., )]. In particular, rats rapidly decrease or increase their energy intake when switched to HP or HFHS diets, respectively, without a significant change in their body weight (Darcel et al ., ; la Fleur et al ., ). In this experiment, the group under HFHS diet was therefore introduced as a point of comparison with HP diet, under the hypothesis that contrasted c‐Fos activations would provide stronger clues to the regions implicated in the specific effects of HP diet.…”
Section: Discussionmentioning
confidence: 99%
“…enough to overcome changes in food intake related to novelty and differences in palatability (Jean et al ., )]. In particular, rats rapidly decrease or increase their energy intake when switched to HP or HFHS diets, respectively, without a significant change in their body weight (Darcel et al ., ; la Fleur et al ., ). In this experiment, the group under HFHS diet was therefore introduced as a point of comparison with HP diet, under the hypothesis that contrasted c‐Fos activations would provide stronger clues to the regions implicated in the specific effects of HP diet.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of vagal afferent pathways in protein sensing and signalling to the brain is supported by results showing that intraduodenal protein activates vagal afferent fibres, and HP feeding induces c-Fos expression in neurons within the NTS (95,96) . Faipoux et al (97) showed that a reduction in food intake after a HP load (v. a NP load) resulted from activation of the noradrenergic neurons related to CCK-induced anorexia.…”
Section: Protein-induced Reduction In Eating and Central Neuronal Patmentioning
confidence: 94%
“…Thus, there is ample evidence that these neuronal populations classically associated with energy sensing are also responsive to amino acids. Beyond the hypothalamus, there is also evidence supporting a role for brain stem neurons in mediating the effect of protein, as both the nucleus of the solitary tract (NTS) appears to contribute to the effects of intracerebroventricular leucine, and also to respond to dietary protein (12,28,39,117).…”
Section: Physiological Signals Of Proteinmentioning
confidence: 99%